2021
DOI: 10.1021/acs.joc.1c02300
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(III)-Catalyzed Cascade Reactions of Imines/Imidates with 4-Hydroxy-2-alkynoates to Synthesize Regioselective Furanone-Fused Isoquinoline Scaffolds

Abstract: A regioselective synthesis of furanone-fused isoquinoline heterocycles is developed in a single step using a Rh(III) catalyst. In this reaction, a cascade C−H activation, regioselective annulation, and lactonization occur in one pot. A wide range of alkynoates was examined, which showed good regioselectivity. The regioselectivity was guided by steric bulk at the C4 position of the 4-hydroxy-2-alkynoates. The synthetic utility was exemplified, and the model reaction was scaled up to a 1 g scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Prabhu and his group reported the synthesis of furanone‐fused isoquinolines 149 via a cascade Rh‐catalyzed cyclization/lactonization, starting from benzimidates 147 or imines and 4‐hydroxy‐2‐alkynoates 148 [70] . Regarding the use of imidates, the desired products 149 emerged in poor yields, as opposed to the imines where good to excellent reaction yields were observed (Scheme 40b).…”
Section: Diverse Applications Of Imidatesmentioning
confidence: 99%
“…Prabhu and his group reported the synthesis of furanone‐fused isoquinolines 149 via a cascade Rh‐catalyzed cyclization/lactonization, starting from benzimidates 147 or imines and 4‐hydroxy‐2‐alkynoates 148 [70] . Regarding the use of imidates, the desired products 149 emerged in poor yields, as opposed to the imines where good to excellent reaction yields were observed (Scheme 40b).…”
Section: Diverse Applications Of Imidatesmentioning
confidence: 99%
“…Very recently, in 2021, K. R. Prabhu and research group [43] in their work reported Rhodium (III) catalyzed cascade reaction for the synthesis of fused Isoquinoline derivatives ( 114 ) from benzimidate ( 112 ) and various 4‐Hydroxy‐2‐alkynoates ( 113 ). Ethyl benzimidate and dimethyl‐substituted 4‐hydroxy‐2‐alkynoates when stirred for 16 h at 120 °C in presence of 5 mol % of [Cp * RhCl 2 ] 2 , 20 mol% of AgSbF 6 , 2.2 equivalent of Cu(OAc) 2 .…”
Section: Alkyne As Coupling Partnermentioning
confidence: 99%
“…[25] In 2011, Ihara and co-workers reported the annulation of imidates (42) with dimethyl acetylenedicarboxylate ( 44 49) in moderate to good yields (Scheme 20). [26] Based on different controlled experiments, it was revealed that cyclic imidates (imino ether) (42) were isomerized to enaminoethers (43) and attacked to alkene systems to yield the Micheal adducts. The adducts then isomerized to enamino ethers followed by cyclization by eliminating methanol as the by-product.…”
Section: Alkene As Coupling Partnermentioning
confidence: 99%
“…[7] Lately, a regioselective synthesis of furanonefused isoquinoline was developed using Rh III catalyst involving a one pot sequence of CÀ H activation, regioselective annulation and lactonization (Scheme 1D). [8] Obviously, it appears that a straightforward strategy allowing a general access to various 3-or 3,3-disubstituted pyridinyllactones is not available yet. Thus, in this context, we report herein our investigation on the synthesis of 3-substituted or 3,3-disubstituted pyridinyl-lactones, based on the condensation of the organometallic ethylnicotinate intermediate on carbonyl derivatives and the subsequent lactonization.…”
Section: Introductionmentioning
confidence: 99%
“…More recently furo[3,4‐ b ]quinolinones were synthesized from 2‐(1‐ethoxyalkoxy)‐3‐cyanoquinolines via sequential removal of acetal protection and intramolecular cyclization/hydration (Scheme 1C) [7] . Lately, a regioselective synthesis of furanone‐fused isoquinoline was developed using Rh III catalyst involving a one pot sequence of C−H activation, regioselective annulation and lactonization (Scheme 1D) [8] …”
Section: Introductionmentioning
confidence: 99%